2022
DOI: 10.1186/s10020-022-00453-0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of dopamine receptor D1 promotes osteogenic differentiation and reduces glucocorticoid-induced bone loss by upregulating the ERK1/2 signaling pathway

Abstract: Background The inhibition of osteogenic differentiation is a major factor in glucocorticoid-induced bone loss, but there is currently no effective treatment. Dopamine, a major neurotransmitter, transmits signals via five different seven-transmembrane G protein-coupled receptors termed D1 to D5. Although the relevance of the neuroendocrine system in bone metabolism has emerged, the precise effects of dopamine receptor signaling on osteoblastogenesis remain unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
(32 reference statements)
1
16
0
Order By: Relevance
“…In this study, we found that in the osteolytic model, the bone density of the skull was reduced, the bone trabeculae were sparse, and the bone mass was reduced. ALP analysis and ARS staining confirmed a reduction in bone formation during bone dissolution induced by wear particles, which is consistent with our previous report [ 26 ]; osteogenesis inhibition is one of the main causes of PPO, and reducing hypogenesis around prostheses induced by wear particles is a key factor in the prevention and treatment of PPO.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we found that in the osteolytic model, the bone density of the skull was reduced, the bone trabeculae were sparse, and the bone mass was reduced. ALP analysis and ARS staining confirmed a reduction in bone formation during bone dissolution induced by wear particles, which is consistent with our previous report [ 26 ]; osteogenesis inhibition is one of the main causes of PPO, and reducing hypogenesis around prostheses induced by wear particles is a key factor in the prevention and treatment of PPO.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous studies also showed that DA treatment can prevent osteolysis caused by wear debris by inhibiting RANKL-dependent osteoclast formation and the inflammatory response mediated by DA-like receptors [ 24 ]. Recent studies have shown that DA can affect the proliferation and osteogenic differentiation of BMSCs through dopamine first receptor (D1R) [ 25 , 26 ]. Whether the regulation of DA receptors can alter bone formation in titanium-induced osteolysis is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Bone growth is regulated by specialized cell types known as osteoblasts, which produce matrix products and transport minerals to form and reshape bone, and osteoclasts, which are macrophage-like cells that are responsible for breaking down bone tissue. Numerous studies show that both osteoblasts and osteoclasts express all subtypes of dopamine receptors, although the receptor profile varies between the two cell types ( Hanami et al, 2013 ; Lee, Tsang et al, 2015; Yang et al, 2016 ; Motyl et al, 2017 ; Handa et al, 2019 ; Wang, Han et al, 2021 ; Zhu et al, 2022 ). For example, RNA sequencing analyses of human and murine osteoblasts and osteoclasts confirmed gene expression of all dopamine receptors and showed increased expression of Drd1, Drd2, and Drd3 during osteoclastogenesis, while mouse osteoblast precursors and mature osteoblasts expressed higher levels of Drd3 and Drd4 ( Handa et al, 2019 ).…”
Section: Regional and Disease-specific Effects Of Dopaminementioning
confidence: 99%
“…Treatment with dopamine (5 × 10 −5 M) increased the proliferation of the immature murine osteoblast cell line MC3T3-E1 (Lee, Tsang et al, 2015), although in another study using this cell line, dopamine suppressed osteoblast mineralization and osteoblast marker expression that was not seen in primary murine osteoblasts ( Motyl et al, 2017 ). Treatment with SKF38393 (D1-like receptor agonist) increased osteoblast differentiation and expression of osteogenic genes in both bone marrow–derived stem cells and MC3T3-E1 ( Zhu et al, 2022 ). In both studies these effects were blocked by treatment with the D1-like antagonist SCH23390, either alone or in combination with the D3 receptor antagonist GR103691.…”
Section: Regional and Disease-specific Effects Of Dopaminementioning
confidence: 99%
See 1 more Smart Citation